Protective role of silibinin in cadmium induced changes of acetylcholinesterase, ATPases and oxidative stress in brain of albino wistar rats - Srinivasan, R; Ramprasath, C (Journal of Ecobiotechnology, 2012)
Cadmium (Cd) a highly toxic metal is considered to be a multitarget toxicant, principally its accumulates in the liver, kidney and hardly get into the brain parenchyma by the brain-barrier system. In this study, Cd (3 mg/kg body weight (b. w.)) was subcutaneously administered to rats for 3 weeks, which shows significantly (P<0.05) increase acetylcholinesterase enzyme activity, with significant elevation of lipid peroxidation along with significant (P<0.05) decreased in the levels of antioxidants and ATPases enzymes in the brain. Oral administration of silibinin (SB) at 80 mg/kg b. w. significantly normalized the acetylcholinesterase activity and reduced the levels of lipid peroxidation and also restored the antioxidant and ATPases enzymes in the brain when compared to other doses of SB (20 and 40 mg/kg b.w.). From this study we conclude that SB improves the changes in acetylcholinesterase, ATPases and oxidative injury by Cd- induced in brain.Â Â